Energy Transition and Energy Democracy in East Asia - Asuka, Jusen; Jin, Dan (Springer Nature Singapore : Imprint: Springer, 2022)
This is an open access book. The subject of this book is to provide down-to-earth information on what kind of actions are being taken by the Government, Local community, Businesses, Researchers, NGOs on the energy transition in this region. It gives an updated picture of the energy transition in the East Asian countries, where the economic growth, as well as CO2 emission growth, is significant. This book focuses not only on the technological perspective of the energy transition but also on the relationship between democracy and energy transition. Readers of this book can understand what kind of international support and pressure is needed to promote the energy transition in this region. Since energy transition is needed not only for combatting climate change but also for the Green Recovery from the COVID-19 pandemic, publishing this book is very helpful to promote the Green Recovery and the Green New Deal world-widely.